TINJAUAN KRIMINOLOGI TERHADAP PROSTITUSI ONLINE DI KALANGAN MAHASISWI (STUDI KASUS PADA MAHASISWI X DAN Y DI KOTA PEKANBARU) - Novarizal, Riky; Soares, Romano (SISI LAIN REALITA, 2021)
Pekanbaru known as the city of the business, many youth and also students who comes to Pekanbaru to looking for the experience and knowledge to reach their goal and ambition, on their  life every human definitely can’t escape from the norm and religious rules which that regulated by the community especially in Pekanbaru City, however in Pekanbaru City there is also a darkside for the college women who had wrong to use their social media and then they are fall into the delinquent crimes. The methods which that used from the researcher are qualitative methods with the essay research which is descriptive and analizing. And also researcher used the Differential Association Theory, Interview and collecting the data will analyze the interview documents which is commited by researcher. Due to the phenomena and factor which is occured on college women which that first is financial and the second is lack of parental attention and the third is promiscuity, however as we know the online media are evolved and then the crimes are happen again and increased so high, like the prostitution problem that occured especially on their environment, so that the problem makes the researcher interested to research and looking for the accurate data source based from trusted fact.